Byproduct from Triphala Extraction as Tannin and Rutin Sources for Production of Gallic Acid, Isoquercetin and Quercetin by Solid-State Fermentation - Teerin Chysirichote; Pattarabhorn Pakaweerachat (My University, 2022)
Byproduct from Triphala extraction process (BTP) was studied as a substrate for gallic acid, isoquercetin and quercetin production by Aspergillus niger fermentation in this research.The results showed that BTP was a good source of tannin and rutin.Neverthe less, the activity of A. niger on BTP as a sole substrate was very low.Supplementing nitro gen sources was found to be a key to enhancing conversion of tannin to gallic acid, and rutin to isoquercetin or isoquercetin and quercetin.BTP with 0.75 % sodium nitrate was sug gested to be an optimal supplemented nitrogen source for the production of gallic acid and isoquercetin in this research, which yielded the highest contents of 61.6±2.16mg g -1 DS and 3.27±0.29mg g -1 DS , respectively.In addition, the highest extraction yields of gallic acid, isoquercetin and quercetin were obtained by an ultrasoundassisted extraction using methanol as an extraction solvent as 12.24±2.12mg g -1 DS which was around 0.5 time higher than the one without ultrasoundassisted extraction (8.84±1.12mg g -1 DS ).
Keywords: Tannin; Tannin, Tannase and Anticancer Activities